Modulation of ABA responses by the protein kinase WNK8 - Waadt, Rainer; Jawurek, Esther C.; Krebs, Melanie; Schumacher, Karin (FEBS letters, 2019)
Abscisic acid (ABA) regulates growth and developmental processes in response to limiting water conditions. ABA functions through a core signaling pathway consisting of PYR1/PYL/RCAR ABA receptors, type 2C protein phosphatases (PP2Cs), and SnRK2-type protein kinases. Other signaling modules might converge with ABA signals through the modulation of core ABA signaling components. We have investigated the role of the protein kinase WNK8 in ABA signaling. WNK8 interacted with PP2CA and PYR1, phosphorylated PYR1 in vitro, and was dephosphorylated by PP2CA. A hypermorphic wnk8-ct Arabidopsis mutant allele suppressed ABA and glucose hypersensitivities of pp2ca-1 mutants during young seedling development, and WNK8 expression in protoplasts suppressed ABA-induced reporter gene expression. We conclude that WNK8 functions as a negative modulator of ABA signaling.
Available online 28 December 2018
Gesehen am 10.04.2019